Dilemma and strategies for production of diesel-like hydrocarbons by deoxygenation of biomass-derived fatty acids - Hongju Lin; Xiyan Chen; Yanchang Chu; Jie Fu; Le Yang (Green Energy & Environment)
The valorization of biomass to produce biofuels has become a heavily investigated field due to the depletion of fossil fuels and environmental concerns. Among them, the research on deoxygenation of fatty acids or esters derived from biomass as well as municipal sludge organics to produce diesel-like hydrocarbons has become a hot topic. Fatty acid is a key intermediate derived from ester hydrolysis, therefore has attracted more attention as a model compound. In this review, we first introduce and compare the three reaction pathways of hydrodeoxygenation, decarboxylation and decarbonylation, for the deoxygenation of fatty acids and esters. The preference of reaction pathway is closely related to the type of raw materials and catalysts as well as reaction conditions. The special purpose of this review is to summarize the dilemma and possible strategies for deoxygenation of fatty acids, which is expected to provide guidance for future exploration and concentrates. The atom utilization along with stability during reaction in a long time is the most important index for commercial economy. Herein, we propose that the rational design and delicate synthesis of stable single-atom non-noble catalysts may be the best solution. The ultimately goal is aiming to develop sustainable production of green diesel hydrocarbons.